Analisis In Silico Potensi Aktivitas Biologis Senyawa Volatil Asap Cair Tempurung Kelapa - Muhammad Andre Reynaldi; Rafika Sari; Abdurraafi’ Maududi Dermawan; Enggy Erwansani; Shahiroh Haulaini; Aulia Faradilla (Indonesian Journal of Herbal and Biomedical Research, 2026)
Coconut shell liquid smoke contains various volatile compounds with potential biological activities that can be explored through computational approaches. This study aimed to predict the potential biological activities of volatile compounds identified in coconut shell liquid smoke using the PASS Online platform as an initial computational screening approach to identify promising natural bioactive compounds for further pharmacological investigation and drug discovery. Five representative volatile compounds reported in previous studies, namely 2-hydroxymethylphenol, 3-methoxybenzene-1,2-diol, 2-methoxyphenol, 2,6-dimethoxyphenol, and 4-methyl-1,2-benzenediol, were selected for analysis. Prediction of biological activities was performed using PASS Online based on the probability of activity (Pa) and probability of inactivity (Pi) values. The results showed that all compounds exhibited high potential biological activities with Pa values above 0.900. The dominant predicted activities included aspulvinone dimethylallyltransferase inhibitor, feruloyl esterase inhibitor, JAK2 expression inhibitor, membrane integrity agonist, and ubiquinol-cytochrome-c reductase inhibitor. Several compounds also demonstrated potential activities related to anti-inflammatory and antimicrobial mechanisms. The predicted activity profiles suggest that volatile phenolic compounds in coconut shell liquid smoke may represent promising candidates for further bioactivity exploration. However, these computational predictions require experimental validation through in vitro and in vivo studies before their biological potential can be confirmed.